HUBUNGAN ANTARA ANEMI DAN STATUS BESI DENGAN STATUS IMUNITAS PADA ANAK YANG MENDAPAT VAKSINASI CAMPAK - Susi Suwarti Suwardi; Ance Murdiana Dahro; Sri Martuti; Reviana Christiani; Muhilal Muhilal (Persagi, 2000)
THE RELATIONSHIP BETWEEN ANEMIA AND IRON STATUS WITH IMMUNE STATUS OF CHILDREN VACCINATED WITH MEASLES VACCINE.Background: Anemia, especially caused by iron deficiency, is one of several health problems in Indonesian children below 5 years of age. That condition seems appear in young children whose food is lack of iron. When those children are going to be vaccinated, how will the result be?.Objective: We sought to determine the relationship between anemia and iron with immune status of children who have got measles vaccine.Method: The study was conducted in village of Bantarjaya district of Bogor, from June 1997 to February 1998 in 86 children above 9 months old who received measles vaccines in local Post Integrated Service (Posyandu). Before intervention, data on physical examination, weight, height, hemoglobin, hematocrit serum ferritin, free erythrocyte protoporphyrin (FEP) and measle immunoglobin G were obtained from all Subjects. Information on morbidity, socioeconomic, environment and food consumption also were recorded. After intervention or six mouths later, the same data were collected again.Results: Subjects were divided into two group; (1) anemic group (Hb<11 g/dl) consisting of 46 subjects (53,5%) and (2) non anemic group (Hb>11 g/dl) with 40 subjects (45,5%). The study revealed that 27,9% subjects have iron deficiency and 43,0% suffered from iron deficiency anemia. Six months after vaccination, the level of measles IgG was increased in 87,4% subjects. The measle IgG level of the non anemic group was increased significantly, but was not significant for the anemic group.Conclusions: There were no relationship between iron status and immune status but however anemic condition influenced the level of measles IgG.Key Words: iron status, anemia, immunoglobulin G.